1989
DOI: 10.1104/pp.90.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Copper Toxicity Affects Photosystem II Electron Transport at the Secondary Quinone Acceptor, QB

Abstract: The nature of Cu2+ inhibition of photosystem 11 (PSII)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 22 publications
7
62
1
2
Order By: Relevance
“…These data are in accordance with those reported by other authors (Shioi et al 1978b, Bohner et al 1980. Hsu and Lee 1988, Samson et al 1988, Mohanty et al 1989. A 50% inhibition of Fv occurred in the presence of ~20 μM CuCl 2 , whereas only~7 30% of PSII are able to emit variable fluorescence after treatment with 40 μM , that could correspond to the extrinsic proteins that stabilise the oxygen-evolving complex and regulare its activity (Enami et al 1989, Hankamer and Barber 1997.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These data are in accordance with those reported by other authors (Shioi et al 1978b, Bohner et al 1980. Hsu and Lee 1988, Samson et al 1988, Mohanty et al 1989. A 50% inhibition of Fv occurred in the presence of ~20 μM CuCl 2 , whereas only~7 30% of PSII are able to emit variable fluorescence after treatment with 40 μM , that could correspond to the extrinsic proteins that stabilise the oxygen-evolving complex and regulare its activity (Enami et al 1989, Hankamer and Barber 1997.…”
Section: Resultssupporting
confidence: 82%
“…Both the acceptor and donor side have been proposed as copper-inhibitory sites. On the PSII reducing side, the Q B binding site (Mohanty et al 1989) and the Pheo-Fe-Q A , domain (Yruela et al 1991(Yruela et al , 1992(Yruela et al , 1993(Yruela et al , 1996a have been reported as the most sensitive sites for Cu(II) toxicity. In addition, the copper ion was shown to impair the function of the oxidising side ( Cedeño-Maldonado and Swader 1972, Vierke and Struckmeier, 1977, Shioi et al 1978a,b, Bohner et al 1980, Samuelsson and Öquist 1980.…”
Section: Introductionmentioning
confidence: 99%
“…DF has been used in research of metals' effects on photosynthesis of algae and higher plants [19,25,26]. Simple, reliable and rapid measurements as well as minimal sample manipulation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors relate the target of the Cu-inhibition of PSII to its oxidizing side [7,54,55]. At higher copper concentrations, primary quinone acceptor QA [27], pheophytin-QA-Fe region [70], non-haem iron [28], and secondary quinone acceptor QB [44] were identifed as the target sites of Cu inhibitory action on the acceptor side of PSII (Fig. 4).…”
Section: Plants and Algaementioning
confidence: 99%